Paliativos jurisprudenciales y notariales a la transmisión mortis causa de la vivienda a favor de menores que no la ocupan - Pérez Gallardo, Leonardo (2020)
In the last years, the Chamber on Civil and Administrative Matters of the People?s Supreme Court, construing inmobiliary law to protect childrens rights, has propitia-ted the transmission of ownership on personal property homes to them, even when children are heirs or legataires not occupying the house at the moment of the owners death; all this under the idea by which lack of legal capacity in minors, patria potestas and tutorship they are all submitted to forbid them to freely determine the place of residence, therefore, the phisycal occupation of the home. This position has also been assumed by the Direction of Civil Registers and Notaries in cases where the heir child not occupying the home has the consent of those heirs actually occupying it.